A comparative study of the entrepreneurial motivation of undergraduate and graduate students in Japan. Issue 2 (April 2021) - Kanama, Daisuke
As entrepreneurs and start-ups have become increasingly significant components of world economic growth, Japan has enacted and discussed various policies to spur entrepreneurship. However, scant attention has been paid toward motivating its youth to embrace the entrepreneurial spirit. Therefore, this study focuses on undergraduate and graduate students and investigates their motivations to become entrepreneurs. The study has three findings. First, the entrepreneurial motivation of Japanese students ranks lower than that of students in the USA, China, India, Spain and Belgium. Second, compared to the motivations of students in other countries, Japanese students' motivations to launch start-up businesses are few in terms of leadership and independence but many in terms of social contribution. Third, Japanese students believe that their lack of business knowledge and competence creates significant risks and barriers to launching start-up businesses. Finally, the paper discusses the impact of culture and barriers on entrepreneurial innovation in Japan compared to other countries.